The economics of water management in developing countries problems, principles and policies - Symposium on Water Resource Management--Efficiency, Equity, and Policy (2000 : Nicosia, Cyprus); Koundouri, Phoebe, 1974-; Edward Elgar Publishing (Cheltenham ; Northhampton, Mass. : Edward Elgar, 2003)
The increasing scarcity of water resources (in terms of quantity and quality) is one of the most pervasive natural resource allocation issues facing development planners throughout the world. This problem is especially prevalent in less developed countries where the management of this valuable resource has become a critical policy concern. This authoritative new volume outlines the fundamental principles and difficulties that characterise this challenging task. The authors begin by detailing the significant problems of water management which are specific to developing countries. In particular, they highlight the political economy of water management in the context of both pricing and institutional reform.
pt. 1. Principles : water management issues surveyed -- pt. 2. Problems : case studies of special difficulties in developing countries -- pt. 3. Policies : a case study of policy making for water management in Cyprus.
Papers presented at the Symposium on Water Resource Management--Efficiency, Equity, and Policy held in Nicosia, September 22-24, 2000.
Includes bibliographical references and index.
Keywords: Water resources development -- Economic aspects -- Developing countries -- Congresses; Electronic books